Organic farming support is an effective and cost-efficient measure to reach sustainability objectives in agriculture policies. Organic farming having environmental and social concerns therefore it has a better market demand. The paper discuss the costs an - Rani, Saima; Khan, Muhammad Azeem; Shah, Hassnain; Anjum, Abdul Sattar (Asian Journal of Agriculture and Rural Development, 2013)
Organic farming support is an effective and cost-efficient measure to reach sustainability objectives in agriculture policies. Organic farming having environmental and social concerns therefore it has a better market demand. The paper discuss the costs and returns structures in the production of vegetables (Cauliflower, Radish and Turnip) grown under the National Institute of Organic Agriculture (NIOA) at National Agriculture Research Centre. Therefore the aim of the paper is to determine the cost of production and estimate the profitability of different selected vegetables. The results indicate that yield of the vegetables was low but the prices of the vegetables were high. All the organic vegetables produce at the NIOA earn positive income without the land rent. In the production of the radish and turnip more labour used as compare to the cauliflower due to the picking of the vegetables. Cost –Benefit ratio was 1.43, 1.35 and 0.85 for turnip, radish and cauliflower respectively. The paper concludes that organic vegetables are profitable but less than the conventional vegetables. But it is hard to measure the profitability of organic vegetables due to the value of unseen indirect benefits.